Upper Primary School Children’s Cosmogonic Ideas: Childhood and Space - Tomašević, Milan (Bulletin of the Institute of Ethnography SASA, 2022)
This paper collates research on the ideas about the origin of the universe and the planet Earth that pupils from Years 5 to 8 of primary school in Belgrade have. Such knowledge should open space for us to further analyse the attitude of young people towards science and the world it describes. With them, it is possible to gain a better insight into the basic ideas about reality that people build and adopt in general. The starting hypothesis is that pupils themselves create hybrid concepts that combine knowledge from classes, ideas from popular culture, and modern scientific theories that are available to them through various media. The cosmological knowledge offered to pupils in geography classes will be analysed, along with the popular discourse accessible to young people. Finally, a preliminary ethnographic study of pupils’ cosmogonic ideas conducted on a pilot sample will be presented. The aim of the research is to understand the pupils’ fundamental knowledge about reality, about the formation of a cognitive framework in which pupils inscribe their own ideas about the place of the Earth and life in space.